2012
DOI: 10.1111/j.2047-2927.2012.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of left varicocoele with height, body mass index and sperm counts in infertile men

Abstract: SUMMARYThe aim of this study was to evaluate interrelation of left varicocoele with height, body mass index (BMI) and sperm counts. We retrospectively evaluated the data of all patients who consulted for infertility at a tertiary academic referral centre from 2000 to 2010. Patient's height, weight, BMI, semen analysis, presence or absence of varicocoele and varicocoele side and grade were evaluated. In statistical evaluations chi-square, student's t, Mann-Whitney U, ANOVA and logistic regression analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 19 publications
2
38
0
2
Order By: Relevance
“…Previous studies have assessed the association between varicocoele and other factors such as age, height, body mass index (BMI), lifestyle habits and occupation (Delaney et al, 2004;Handel et al, 2006;May et al, 2006;Nielsen et al, 2006;Prabakaran et al, 2006;Tsao et al, 2009;Chen & Huang, 2010;Bae et al, 2014;Shafi et al, 2014). Some studies suggested that BMI was inversely associated with the prevalence of varicocoele (Handel et al, 2006;May et al, 2006;Nielsen et al, 2006;Prabakaran et al, 2006;Tsao et al, 2009;Chen & Huang, 2010;Baek et al, 2011;Gokce et al, 2013;Rais et al, 2013), whereas other studies found no such relationship (Oster, 1971;Delaney et al, 2004;Bae et al, 2014;Shafi et al, 2014). Some studies suggested that BMI was inversely associated with the prevalence of varicocoele (Handel et al, 2006;May et al, 2006;Nielsen et al, 2006;Prabakaran et al, 2006;Tsao et al, 2009;Chen & Huang, 2010;Baek et al, 2011;Gokce et al, 2013;Rais et al, 2013), whereas other studies found no such relationship (Oster, 1971;Delaney et al, 2004;Bae et al, 2014;Shafi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have assessed the association between varicocoele and other factors such as age, height, body mass index (BMI), lifestyle habits and occupation (Delaney et al, 2004;Handel et al, 2006;May et al, 2006;Nielsen et al, 2006;Prabakaran et al, 2006;Tsao et al, 2009;Chen & Huang, 2010;Bae et al, 2014;Shafi et al, 2014). Some studies suggested that BMI was inversely associated with the prevalence of varicocoele (Handel et al, 2006;May et al, 2006;Nielsen et al, 2006;Prabakaran et al, 2006;Tsao et al, 2009;Chen & Huang, 2010;Baek et al, 2011;Gokce et al, 2013;Rais et al, 2013), whereas other studies found no such relationship (Oster, 1971;Delaney et al, 2004;Bae et al, 2014;Shafi et al, 2014). Some studies suggested that BMI was inversely associated with the prevalence of varicocoele (Handel et al, 2006;May et al, 2006;Nielsen et al, 2006;Prabakaran et al, 2006;Tsao et al, 2009;Chen & Huang, 2010;Baek et al, 2011;Gokce et al, 2013;Rais et al, 2013), whereas other studies found no such relationship (Oster, 1971;Delaney et al, 2004;Bae et al, 2014;Shafi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is a common cause of male infertility (Miyaoka & Esteves, 2012). Population-based studies, largely school and military screening physical examination data, have shown that the prevalence of varicocoele is approximately 3.58-25.4% in the general population (Oster, 1971;Steeno et al, 1976;Stavropoulos et al, 2002;Kumanov et al, 2007;Baek et al, 2011;Rais et al, 2013;Alsaikhan et al, 2016), 21-41% in men with primary infertility and 75-81% in men with secondary infertility (World Health Organization, 1992;Gorelick & Goldstein, 1993;Jarow, 2001; Gokce et al, 2013). The prevalence varies according to the population characteristics, examination method and regions.…”
Section: Introductionmentioning
confidence: 99%
“…Our study shows that the degree of varicocele and testicular volume are not predictive factors. Some data in the literature have found that the frequency of varicocele in the population is negatively correlated with BMI (Gokce et al, 2013) and that being overweight is a risk factor for oligoasthenospermia (Sermondade et al, 2013); our study showed that BMI is negatively correlated with the seminal outcome, but it is not a predictor of seminal outcome. The association between FSH and seminal improved outcome is controversial; some studies claim that patients with normal FSH, pre-intervention, get better results, while those with higher values have little or no room for improvement (Pasqualotto et al, 2003), and other authors say that low initial levels of FSH are associated with a better seminal outcome (Kondo et al, 2009).…”
Section: Discussionmentioning
confidence: 62%
“…After these analyses, six studies were removed and there were 13 articles containing seven case-control studies (Chanc Walters, Marguet, & Crain, 2012;Chen & Huang, 2010;Gorur et al, 2015;Handel, Shetty, & Sigman, 2006;Kılıç et al, 2007;Liu et al, 2015;Shafi & Agajani, 2015) and six observational crosssectional studies (Gokce, Demirtas, Ozturk, Sahin, & Ekmekcioglu, 2013;Liu et al, 2017;Rais et al, 2013;Söylemez, Atar, Sancaktutar, Bozkurt, & Penbegül, 2011;Tsao et al, 2009;Yigitler, Yanardag, Silit, & Alpay, 2012) remained. Among these relevant investigations, 144 different articles were obtained without duplication.…”
Section: Eligible Studiesmentioning
confidence: 99%